Determinants of Public Debt Ratio in Middle-Income Countries - Ghania Atiqasani; Nairobi Nairobi; Arif Darmawan (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The existence of the Covid-19 pandemic, which hampers mobility and productivity, creates a slowdown in the movement of the wheels of the economy, thus indirectly requiring several countries to increase their sources of revenue through public debt to meet the needs of the people and maintain economic stability in each country. the problems faced by middle-income countries are related to the participation of government and other public institutions both in the formulation of public policies, the management of public resources, to the realization of human rights that should be free from abuse of the position of relevant policymakers. As a result, not a few countries experience uncertainty about the actual situation from public accounts, which has encouraged the creation of doubts and conflicts among the public about the role of governments in dealing with the global economic crisis, which among others, is illustrated through several economic problems that occur in middle-income countries. The purpose of this study is to answer the question of whether, in middle-income countries, the factors of the previous year's debt-to-GDP ratio, fiscal transparency, corruption, and e-budgeting simultaneously and partially influence the debt-to-GDP balance in 74 middle-income countries in 2021. The method used is OLS regression analysis of cross-section data. This study found that the previous year's debt accumulation significantly affected the debt ratio to GDP. Meanwhile, fiscal transparency and the implementation of e-budgeting hurt the insignificant debt-to-GDP ratio; corruption has a little positive effect on the debt-to-GDP ratio.